Technological exploitation of the JET neutron environment: progress in ITER materials irradiation and nuclear analysis. (14th October 2021) - Packer, L.W.; Batistoni, P.; Bekris, N.; Bradnam, S.C.; Fabbri, M.; Ghani, Z.; Gilbert, M.R.; Kierepko, R.; Łaszyńska, E.; Leichtle, D.; Lengar, I.; Loreti, S.; et al.
Abstract: Several experimental activities have been conducted within the 'ACT' sub-project under the EUROfusion WPJET3 programme with the purpose to ultimately irradiate ITER materials within the JET D–T neutron environment. The latest results of these activities are presented in this work. The ITER materials include: poloidal field coil jacket samples and toroidal field coil radial closure plate steels, EUROFER 97-2 steel, W and CuCrZr materials from the divertor, Inconel 718, CuCrZr and 316L stainless steel for blanket modules and vacuum vessel forging samples. The experimental results presented here include gamma spectrometry measurements and analysis obtained from post-irradiated samples following the 2019 C38 (D–D) campaign, where a total of 97 samples were irradiated in a newly prepared long-term irradiation station assembly, comprising 27 ITER material samples, 70 dosimetry foils and two combination-foil detectors, known as 'VERDI' detectors. Measurements using a range of dosimetry reactions that are present in the IRDFF-II nuclear data file have also been used in preparatory work to characterise the irradiation locations. The latest ITER sample measurement results are presented along with initial comparisons with corresponding neutron transport and activation calculation predictions.